2009
DOI: 10.4141/cjps08127
|View full text |Cite
|
Sign up to set email alerts
|

Optical sensors have potential for determining nitrogen fertilizer topdressing requirements of canola in Saskatchewan

Abstract: . Optical sensors have potential for determining nitrogen fertilizer topdressing requirements of canola in Saskatchewan. Can. J. Plant. Sci. 89: 411Á425. An important challenge in N management is matching fertilizer inputs to crop requirements for specific environmental conditions. Field experiments were completed over 3 yr at two locations in Saskatchewan to evaluate the feasibility of using optical sensors and high-N reference plots along with topdressed liquid urea ammoniumnitrate (UAN) to arrive at more op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The NDVI readings of the plant canopy were used in our study to differentiate possible changes in overall plant health among the treatments as it may be considered a proxy for general nutrient uptake [39,40]. The Black Chernozem soil displayed a higher average NDVI than the Dark Grey Luvisol; however, both soils displayed similar trends among treatments.…”
Section: Normalized Difference Vegetation Indexmentioning
confidence: 99%
“…The NDVI readings of the plant canopy were used in our study to differentiate possible changes in overall plant health among the treatments as it may be considered a proxy for general nutrient uptake [39,40]. The Black Chernozem soil displayed a higher average NDVI than the Dark Grey Luvisol; however, both soils displayed similar trends among treatments.…”
Section: Normalized Difference Vegetation Indexmentioning
confidence: 99%
“…12). Holzapfel et al (2009) found that the NDVI data obtained between the six-leaf stage (BBCH 16) and the beginning of flowering (BBCH 60) are correlated with the canola harvest. In this study, correlation results between BBCH 16 and 60 are moderate, but BBCH stages 71 and 77 perform even better.…”
Section: Phenologymentioning
confidence: 99%
“…Using Nitrogen fertilisation optimization technique based on canopy optical reflectance, VRT for N-application in wheat which enhance Nitrogen use efficiency by >15% compared to uniform rate N-application. Biermacher et al [52] and Boyer et al [53] compared the profitability of a sensor based VRT approach for N application with traditional uniform N-application. The system's controller used the optical reflectance data to calculate Napplication rate for each 0.37 m 2 grid on-the-go in situ and Napplication depending on the rate using an algorithm.…”
Section: Real-time Vrt For Fertilizer Applicationmentioning
confidence: 99%